Soft tissue preservation in the Triassic pachypleurosaur Keichousaurus hui: evidence for digestive tract anatomy, diet, and feeding behavior - Li, Ji; Lehrmann, Daniel J.; Luo, Yong-ming; Adams, Thomas L.; Yu, Mei-yi; Liao, Jun-ling; Qin, Yan-jiao; Li, Yu-lan; Wang, Yue (Frontiers in Ecology and Evolution, 2023)
Keichousaurus hui is the most abundant and representative species in the Xingyi biota in South China. K. hui has been studied in many aspects, including its functional morphology, osteology, ontogeny, allometric growth, sexual dimorphism, and reproduction. Previous studies have assumed that Keichousaurus’ anteriorly curved teeth were used to impale prey and to tear and swallow either the whole or partially fragmented prey. Prey items have been assumed to be small fish or soft-bodied invertebrates, such as squid and shrimp, that were also present in the Xingyi biota. However, there has been no direct evidence for the anatomy of the digestive tract or the diet of the Keichousaurus. There are few reports of the soft tissue preservation of K. hui. In this study, we present relatively complete preservation of the digestive tract with food remains in several well-preserved specimens of K. hui. By comparing with modern reptiles, we reconstructed the internal distribution and organ composition of the digestive tract of K. hui. Through the analysis of the alimentary canal remnants by microscope and X-ray computed microtomography, we infer that K. hui was a frequently piscivorous species that usually swallowed its prey whole.